Lack of secondary sexual characters in a male of Tsingymantis antitra confirms its position as most basal mantelline frog lineage - Raselimanana, Achille P.; Glaw, Frank; Vences, Miguel (Zootaxa, 2007)
Among the endemic radiation of mantellid frogs from Madagascar, the recently described genus Tsingymantis is one of the most enigmatic lineages considered to belong to the subfamily Mantellinae (Glaw et al. 2006). Mantellines are characterized by several derived characters related to reproduction: As far as known, they all deposit their eggs outside of the water (Blommers-Schlösser & Blanc 1991; Glaw & Vences 2006). They also lack a strong mating amplexus, and associated to this derived mating behaviour, males also have no nuptial pads or release calls (Blommers-Schlösser & Blanc 1991; Glaw & Vences 1994). In addition, males in the Mantellinae (except for Boehmantis microtympanum and Spinomantis microtis; see Andreone & Nussbaum 2006) have specialized macroglands on the ventral shanks (usually called femoral glands), and in the genera Gephyromantis and Mantidactylus, they often have larger relative tympanum sizes (Glaw & Vences 2006).